Does retrieval activate related words more than presentation? - Hausman, Hannah, author; Rhodes, Matthew G., advisor; Cleary, Anne, committee member; Davalos, Deana, committee member; Burzynska, Agnieszka Z., committee member (Colorado State University. Libraries, 2017)
Retrieving information enhances learning more than restudying. One explanation of this effect is based on the role of mediators (e.g., sand-castle can be mediated by beach). Retrieval is hypothesized to activate mediators more than restudying, but existing tests of this hypothesis have had mixed results (Carpenter, 2011; Lehman & Karpicke, 2016). The present experiments explored different explanations of the conflicting results. The pilot experiment tested—and found no evidence—that the results depended on whether a conceptual or perceptual measure of mediator activation was used. Experiments 1 and 2 tested whether mediator activation during a retrieval attempt depends on the accessibility of the target information. A target was considered less versus more accessible when fewer retrieval versus more cues were given during retrieval practice (Experiment 1), when the target had been studied once versus three times initially (Experiment 2), or when the target could not be recalled versus could be recalled during retrieval practice (Experiments 1 and 2). Although there was a trend for retrieval to activate mediators more than presentation, mediator activation was not reliably related to target accessibility. Thus, Experiments 1 and 2 neither strongly supported, nor disconfirmed, the role of mediators in enhancing learning from retrieval.